Axial compressive behavior of square reinforced concrete columns confined using two layers of stirrups. Issue 8 (August 2016) - Wu, Dong-Yan; Sun, Lin-Zhu; Yang, Fang; Zhao, Jun-Liang; Li, Wei
Reinforced concrete column confined using two layers of stirrups is a new kind of column form recently proposed by the authors. The concrete of the column is under three different levels of confinement, namely unconfined concrete cover, singly confined, and doubly confined concrete core. This column form provides a simple but effective solution for reinforced concrete columns located in seismic hazard zones and/or reinforced concrete columns with large axial load ratio, where large amount of transverse reinforcement is necessary to achieve a ductile response. This study aims to investigate the axial compressive behavior of square reinforced concrete columns confined using two layers of stirrups. In total, 15 columns were prepared and tested under axial compression. Two different stirrup configurations were investigated. The axial responses and the failure modes of the columns were examined in detail, and the average stress–strain curve of the singly confined and doubly confined concrete core was derived. A stress–strain model with satisfactory accuracy was proposed based on the interpretation of test results.